1996
DOI: 10.1037/1061-4087.48.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Coaching executives.

Abstract: This article describes Nordli, Wilson Associates' approach to executive coaching. It is a systemsbased approach that attempts to maximize the consideration of contextual factors. An illustrative case study of this approach is provided. Nordli, Wilson Associates, a full-service psychological consulting partnership with offices inWestborough, Massachusetts^and New Haven, Connecticut. His background is in clinical and consulting psychology. He joined Nordli, Wilson Associates in 1974 and has consulted full-time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 1 publication
0
65
0
6
Order By: Relevance
“…This formal recognition of business coaching as a distinct staff development field of its own came about in the 1980s (Hudson, 1999;Kampa-Kokesch & Anderson, 2001;Kilburg, 1996aKilburg, , 1996bOlesen, 1996;Tobias, 1996). Harris (1999) describes three periods in the history of business coaching.…”
Section: The Practical and Theoretical Development Of Business Coachingmentioning
confidence: 99%
“…This formal recognition of business coaching as a distinct staff development field of its own came about in the 1980s (Hudson, 1999;Kampa-Kokesch & Anderson, 2001;Kilburg, 1996aKilburg, , 1996bOlesen, 1996;Tobias, 1996). Harris (1999) describes three periods in the history of business coaching.…”
Section: The Practical and Theoretical Development Of Business Coachingmentioning
confidence: 99%
“…It was suggested that executive coaching was really a repackaging of activities and techniques borrowed from other disciplines such as counselling, psychology , learning and consulting (Tobias, 1996). It is undoubtedly true that a significant amount of the knowledge base used by coaches originates from other disciplines.…”
Section: Review Of Research: 2000 -2009mentioning
confidence: 99%
“…An ongoing series of activities tailored to the individual' s current issues or relevant problem is designed by the coach to assist the executive in maintaining a consistent, confident focus as he or she tunes strengths and manages shortcomings (Tobias, 1996).…”
mentioning
confidence: 99%